2013
DOI: 10.1074/jbc.m112.410423
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic Acid-dependent Recruitment and Function of the Rac Activator DOCK1 during Dorsal Ruffle Formation

Abstract: Background: DOCK1 is an atypical Rac activator. Results: Activation of the PDGF receptor induces DOCK1 translocation to the dorsal ruffles through association with phosphatidic acid. Blocking of this interaction impairs dorsal, but not peripheral, ruffle formation. Conclusion: Phosphatidic acid acts as a lipid anchor for DOCK1 during dorsal ruffle formation. Significance: A novel regulatory mechanism for dorsal ruffle formation was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Pdgf treatment of fibroblasts promotes a rapid DHR-1-dependent and PIP 3 -dependent recruitment of both Dock1 and Dock5 at the membrane, resulting in the activation of Rac1 to form peripheral ruffles. As in neutrophils, PA production lags behind that of PIP 3 and acts to focus the localization of Dock1 (but not Dock5, as it lacks a PBR) at the membrane to generate the characteristic Pdgf-induced dorsal ruffles (Sanematsu et al 2013). These data highlight the importance of localizing individual Dock family members for specific biological functions.…”
Section: Lipids and Scaffolds: Spatiotemporal Activation Of Docksmentioning
confidence: 86%
See 1 more Smart Citation
“…Pdgf treatment of fibroblasts promotes a rapid DHR-1-dependent and PIP 3 -dependent recruitment of both Dock1 and Dock5 at the membrane, resulting in the activation of Rac1 to form peripheral ruffles. As in neutrophils, PA production lags behind that of PIP 3 and acts to focus the localization of Dock1 (but not Dock5, as it lacks a PBR) at the membrane to generate the characteristic Pdgf-induced dorsal ruffles (Sanematsu et al 2013). These data highlight the importance of localizing individual Dock family members for specific biological functions.…”
Section: Lipids and Scaffolds: Spatiotemporal Activation Of Docksmentioning
confidence: 86%
“…A polybasic region (PBR) (see Fig. 1) in Dock1 and Dock2 was initially thought to bind PIP 3 , but more recent data suggest that it binds the signaling lipid phosphatidic acid (PA) (Kobayashi et al 2001;Nishikimi et al 2009;Sanematsu et al 2013). Insight into the biological role of this second lipid-binding activity Ó 2014 Laurin and Cô té This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml).…”
Section: Lipids and Scaffolds: Spatiotemporal Activation Of Docksmentioning
confidence: 99%
“…For example, DOCK1 and DOCK5, as well as DOCK2, belong to the DOCK-A subfamily and act as Rac-specific GEFs (10,19). DOCK1 and DOCK5 are widely expressed in various tissues and regulate multiple cellular functions, including myoblast fusion, bone resorption, and migration (20)(21)(22); however, their roles in the immune system and immune responses are poorly understood. We found that neutrophils also express DOCK5, but not DOCK1.…”
mentioning
confidence: 99%
“…In PDGF-induced dorsal ruffle formation pathway in mammalian cells, Abl signals to activate Rac [28, 35, 5356]. This activation might involve DOCK180 since the complex of Crk/DOCK180 has been shown to control Rac activation during dorsal ruffle formation [57] (Fig. 4F).…”
Section: Discussionmentioning
confidence: 99%